2010
DOI: 10.1109/tpwrs.2010.2042084
|View full text |Cite
|
Sign up to set email alerts
|

SIMD-Based Large-Scale Transient Stability Simulation on the Graphics Processing Unit

Abstract: This paper presents a single-instruction-multiple-data (SIMD) based implementation of the transient stability simulation on the Graphics Processing Unit (GPU). Two programming models to implement the standard method of the transient stability simulation are proposed and implemented on a single GPU. In the first model the CPU is responsible for part of the simulation, while the onerous computations were offloaded to the GPU, creating a hybrid GPU-CPU simulator. In the second model, the GPU performs all the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 29 publications
0
61
0
Order By: Relevance
“…Time domain EMT simulation is carried out using the following commonly known Nodal equation [1], [17], [12], [18]:…”
Section: Overview Of Emt Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Time domain EMT simulation is carried out using the following commonly known Nodal equation [1], [17], [12], [18]:…”
Section: Overview Of Emt Simulationmentioning
confidence: 99%
“…Using several different test cases, the authors' earlier work [9], showed that GPU-based EMT simulation produces exactly the same result as the commercial tools. Other researchers also used this approach for creating large test cases [5], [12], [13], [30].…”
Section: Test Cases Used For Gpu Based Emt Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the obtained comparison results prove the correctness of computations performed by author's own program. The speed-up of computations (S) done with application of the graphics processing unit (GPU) is defined according to the following relation [32]:…”
Section: Verification Of Numerical Solutionmentioning
confidence: 99%
“…On the basis of the results, the speed-up S is determined. It is assigned according to the following equation [12]:…”
Section: Efficiency Of Computations Conducted On a Graphics Processinmentioning
confidence: 99%